PENGARUH KUALITAS SUMBER DAYA MANUSIA DAN PEMANFAATAN SISTEM INFOMASI TERHADAP SISTEM PENGENDALIAN INTERNAL - Ainul Yusna Harahap; Nurliza Lubis; Syardiansah Syardiansah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2022)
This study aims to determine the effect of the quality of human resources and the utilization of information systems on the internal control system in the Deli Serdang Regency OPD. Data were analyzed using multiple linear regression, reliability test, validity test, normality test, heteroscedasticity test, multicollinearity test, t test and F test. The results of multiple linear regression test obtained Y = 1.652 + 0.173X1 + 0.393X3. Based on the reliability and validity test, all data were declared valid and reliable. And the results of the normality, heteroscedasticity and multicollinearity tests of the data showed normal results, there was no heteroscedasticity and multicollinearity. While the results of the partial test (t test) indicate that the quality of human resources has no significant effect on the internal control system of OPD Deli Serdang Regency but the use of information systems has a significant effect on the internal control system of OPD Deli Serdang Regency. While the results of the simultaneous test (F test) of the quality of human resources and the use of information systems have a significant effect on the internal control system of OPD Deli Serdang Regency. And the results of the coefficient of determination test show that 23.30% of the variables of the quality of human resources and the utilization of information systems can explain the influence of the variables of the internal control system.